2022
DOI: 10.1115/1.4054161
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of the Fan Flutter Mechanism Related to Acoustic Propagation Characteristics

Abstract: In this study, we numerically investigated the flutter mechanism related to acoustic propagation characteristics of a wide-chord fan rotor. We considered the first bending mode and its two and three nodal diameters traveling wave patterns. The unsteady disturbance induced by the blade vibration in the duct gradually changed from cut-off to cut-on mode by increasing the blade frequency. Flutter occurred in some specific frequency range. We observed the upstream cut-on and downstream cut-off condition with the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Gallardo et al [20] reported strong pressure wave interactions between blade rows even with an acoustic cut-off, revealing that multistage decay of acoustic waves may still cause aeroelastic instability of the blades. Dong et al [21] discovered that for a fan, both upstream cut-on and downstream cut-off, as well as both upstream and downstream cut-off, can induce blade flutter. When the blade vibration frequency is at the upstream acoustic resonance, the blade aeroelastic stability significantly increases.…”
Section: Introductionmentioning
confidence: 99%
“…Gallardo et al [20] reported strong pressure wave interactions between blade rows even with an acoustic cut-off, revealing that multistage decay of acoustic waves may still cause aeroelastic instability of the blades. Dong et al [21] discovered that for a fan, both upstream cut-on and downstream cut-off, as well as both upstream and downstream cut-off, can induce blade flutter. When the blade vibration frequency is at the upstream acoustic resonance, the blade aeroelastic stability significantly increases.…”
Section: Introductionmentioning
confidence: 99%